2023
DOI: 10.1038/s42005-023-01127-x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine-structure-resolved laser spectroscopy of many-electron highly charged ions

Abstract: Hyperfine structures of highly charged ions (HCIs) are favourable spectroscopic targets for exploring fundamental physics along with nuclear properties. Recent proposals of HCI atomic clocks highlight their importance, especially for many-electron HCIs, and they have been theoretically investigated by refining atomic-structure calculations. However, developments in hyperfine spectroscopy of many-electron HCIs have not proceeded due to experimental difficulty. Here, we demonstrate hyperfine-structure-resolved l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 78 publications
(91 reference statements)
1
9
0
Order By: Relevance
“…Our study complements recent works from other groups that have investigated various interesting ionic species, for instance [22][23][24][25][26][27][28][29][30], using electron beam ion traps (EBITs). These works also emphasized heavy ions, orbital crossings, and hyperfine structure studies (e.g.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our study complements recent works from other groups that have investigated various interesting ionic species, for instance [22][23][24][25][26][27][28][29][30], using electron beam ion traps (EBITs). These works also emphasized heavy ions, orbital crossings, and hyperfine structure studies (e.g.…”
Section: Introductionsupporting
confidence: 73%
“…These works also emphasized heavy ions, orbital crossings, and hyperfine structure studies (e.g. [29] on I VIII). It is interesting to mention here that such hyperfine anomalies in neutrals (see [31] for a recent example, and [32] for a general review) can be tools for searching for New Physics, and that the same applies to HCI as well.…”
Section: Introductionmentioning
confidence: 99%
“…This previous theoretical study suggested that this transition possesses relatively large hyperfine splitting. We consider that this transition is a practical target for the hyperfine spectroscopy under the quasi-Zeeman-free EBIT field, which we have recently demonstrated [17].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the injection methods using an ion source require a sophisticated ion-beam control with specialized ion-beam optics to allow injection along the EBIT axis. MEVVA and laser ablation are time-dependent injection methods, and thus need careful consideration to apply them to time-dependent experiments such as resonant process observations by sweeping the electronbeam energy [16], time-resolved laser spectroscopy [17], and lifetime measurements [18]. While a Knudsen cell connected to an EBIT is versatile for the continuous injection of metals, the melting point of the crucible generally restricts the maximum operating temperature, making vapor generation difficult for metals with extremely low vapor pressure, such as W, Ta, Re, and Nb.…”
Section: Introductionmentioning
confidence: 99%
“…self-energy and vacuum polarization are plays a dominant role in highly charged ions properties. Currently, the active fundamental research areas such as precise measurement of fine structure constant needs accurate atomic clocks based on highly charged ion and these individual QED corrections plays a crucial role in their development [73][74][75].…”
Section: Theoretical Background and Computational Approachmentioning
confidence: 99%